2021
DOI: 10.1002/num.22745
|View full text |Cite
|
Sign up to set email alerts
|

A fully‐mixed finite element method for the coupling of the Navier–Stokes and Darcy–Forchheimer equations

Abstract: In this work we present and analyze a fully-mixed formulation for the nonlinear model given by the coupling of the Navier-Stokes and Darcy-Forchheimer equations with the Beavers-Joseph-Saffman condition on the interface. Our approach yields non-Hilbertian normed spaces and a twofold saddle point structure for the corresponding operator equation. Furthermore, since the convective term in the Navier-Stokes equation forces the velocity to live in a smaller space than usual, we augment the variational formulation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 35 publications
0
1
0
Order By: Relevance
“…Caucao et al [33] found the numerical solution of a nonlinear model that involved the Navier-Stokes and Darcy-Forchheimer equations with the Beavers-Joseph-Saffman condition on the interface. A study involving two dimensional nanofluid flow in the presence of Ohmic dissipations, Darcy-Forchheimer medium and second order slip was carried out by Ganesh et al [34].…”
Section: Introductionmentioning
confidence: 99%
“…Caucao et al [33] found the numerical solution of a nonlinear model that involved the Navier-Stokes and Darcy-Forchheimer equations with the Beavers-Joseph-Saffman condition on the interface. A study involving two dimensional nanofluid flow in the presence of Ohmic dissipations, Darcy-Forchheimer medium and second order slip was carried out by Ganesh et al [34].…”
Section: Introductionmentioning
confidence: 99%